2015
DOI: 10.5586/asbp.2015.032
|View full text |Cite
|
Sign up to set email alerts
|

A simple way to overcome the recalcitrance of the water fern Ceratopteris thalictroides (L.) Brongn. to cryopreservation

Abstract: Ceratopteris thalictroides is a water fern very sensitive to both dehydration and low temperature. This study focuses on the cryopreservation of this species by encapsulation-dehydration technique, in particular on the effects of pre-culture step, alginate bead size and the physical conditions of culture on the cryopreservation efficiency. Encapsulated and non-precultured gametophytes did not survive cooling with liquid nitrogen. When cryopreservation was preceded by a 2-week period of pre-culture, regrowth re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Moreover, distinct and adapted cryogenic techniques have been applied to a wide range of tissues, such as embryogenic tissue cultured in a liquid medium and independent-living autotrophic fern gametophytes, which are capable of sexual reproduction and vegetative propagation, especially under in vitro culture conditions (Rybczyński et al, 2018). Efficient in vitro regeneration systems developed at the Department of Plant Conservation Biology of the PAS BG-CBDC (Rybczyński et al, 2015(Rybczyński et al, , 2018 have provided sufficient tissue for experimental purposes, thus enriching our understanding and enabling the development of highly efficient cryopreservation protocols (Makowski et al, 2015(Makowski et al, , 2016Mikuła et al, 2011Mikuła et al, , 2015Tomiczak et al, 2018). is has allowed for the embryogenic tissues of four species of the genus Gentiana to be introduced into LN and stored successfully for 11 years (Table 1).…”
Section: The Polish Academy Of Sciences Botanical Garden -Center For ...mentioning
confidence: 99%
“…Moreover, distinct and adapted cryogenic techniques have been applied to a wide range of tissues, such as embryogenic tissue cultured in a liquid medium and independent-living autotrophic fern gametophytes, which are capable of sexual reproduction and vegetative propagation, especially under in vitro culture conditions (Rybczyński et al, 2018). Efficient in vitro regeneration systems developed at the Department of Plant Conservation Biology of the PAS BG-CBDC (Rybczyński et al, 2015(Rybczyński et al, , 2018 have provided sufficient tissue for experimental purposes, thus enriching our understanding and enabling the development of highly efficient cryopreservation protocols (Makowski et al, 2015(Makowski et al, , 2016Mikuła et al, 2011Mikuła et al, , 2015Tomiczak et al, 2018). is has allowed for the embryogenic tissues of four species of the genus Gentiana to be introduced into LN and stored successfully for 11 years (Table 1).…”
Section: The Polish Academy Of Sciences Botanical Garden -Center For ...mentioning
confidence: 99%
“…Various cryopreservation methods, such as vitrification (PVS2 and PVS3), encapsulation-vitrification, and encapsulation-dehydration with or without a 7-or 14-day preculture on ABA, were tested for their effectiveness in preserving the viability of a wide range of fern species (Makowski, 2013;Mikuła, Makowski, et al, 2011). e encapsulation-dehydration with preculture on ABA, reduced size of alginate beads from 5 mm to 2.5 mm, and 7 days of darkness during the recovery of post-thaw cultures of gametophytes provided the best results (Makowski et al, 2015). is protocol was subsequently used to prepare the gametophytes of other fern species for long-term banking in the LN (Figure 4).…”
Section: Fernsmentioning
confidence: 99%
“…(Ballesteros et al 2011;Shi 2014, 2015;Mikuła et al 2015c), investigation into the value of using LN focused on the preservation of spore material (Pence 2000b;Ballesteros et al 2011;Barnicoat et al 2011). Some previous studies have shown that the gametophytes of ferns (Pence 2000a(Pence , 2008Mikuła et al 2009Mikuła et al , 2011Barnicoat et al 2011;Makowski et al 2015) and mosses (Schulte and Reski 2004;Pence 2008; Rowntree and Ramsay 2009) can provide a novel and abundant source of material for long-term storage using LN. Gametophytes are highly regenerative following storage under in vitro conditions, and can be recovered from even single living cells of cryopreserved explants (Mikuła et al 2009.…”
Section: Introductionmentioning
confidence: 99%